Social Media as a Learning Tool in Medical Education: A Situation Analysis - Vahe, Mariliis; Zain-Ul-Abdin, Khawaja; Turel, Yalin Kilic (Igi Global, 2012)
Social media has become one of the most dominant information phenomena of our time. As its commercial, social, activist, and informational uses multiply, questions are raised as to its efficiency as a learning tool. The authors focus this chapter on social media use in higher education, specifically in the field of medical education, and provide a modern definition of social media and its tools while elaborating on its educational uses and efficiency. Furthermore, they present a situation analysis through a review of original research published on the topic in the last five years, culminating in an identification of the gaps in literature and recommendations for future research endeavors.
Keywords: Technologies; Internet; Facebook; Twitter; Support